Assessment of Adult Learning Disabilities : A Triangulated Study - Jovita M. Ross-Gordon; Cynthia Plotts; Julie Noble; Autumn Leal; Robert Wells (Adult Education Research Conference, 2001)
The purpose of this roundtable is to discuss North American literature showing how race, class, and gender has been treated historically and presents three approaches or perspectives that inform contemporary literature.